Respuesta :

Hi there!

• f(x) = 3x + 1
• g(x) = x² - 6

Then,
According to th' question :-

(f - g)(x) = f(x) - g(x)

= 3x + 1 - (x² - 6)

= 3x + 1 - x² + 6

= -x² + 3x + 7

Hence,
Option 2ⁿᵈ : -x² + 3x + 7 is Correct.

~ Hope it helps!
[tex] [/tex]

The  [tex](f-g)(x)=-x^{2} +3x+7[/tex]

We have given that

f(x) = 3x + 1 and  g(x) = x² - 6

We have to find (f-g)(x)=?

Now we have (f - g)(x) = f(x) - g(x)  ....(by using distributive property for addition)

What is the distributive property?

(a+b)(x)=ax+bx

Therefore we get,

[tex]= 3x + 1 - (x^2 - 6)\\\\= 3x + 1 - x^2 + 6...(Simplify parenthesis)\\\\= -x^2+ 3x + 7.....(Add like terms)[/tex]

Therefore we get the answer is [tex](f-g)(x)=-x^{2} +3x+7[/tex]

To learn more about the subtraction  of function visit:

https://brainly.com/question/24380382